Input-providing vs. output-pushing corrective feedback in dyadic tutoring sessions. (December 2019) - Netz, Hadar; Fogel, Orna
Abstract: The current study investigates corrective feedback in Torah (Pentateuch) reading dyadic tutoring sessions. In this setting, corrective feedback is invariably explicit, which makes it possible to compare between feedback that is input-providing (recasts and explicit corrections) and output-pushing (prompts), without the confounding factor of feedback im/explicitness. Results indicate that input-providing feedback led to higher frequencies of successful repair than did output-pushing feedback. However, microanalysis revealed that this advantage was usually short-lived, as the pupils typically repeated the original error soon after its successful repair. In contrast, although output-pushing feedback resulted in more forms that still needed repair, microanalysis revealed that following output-pushing, fewer episodes were required until accurate and fluent reading was achieved.